(untitled) (Linguostylistic Studies, 2017)
This paper presents a large set of plant names, identified in the works by Volodymyr Lys. The study reveals the specificity of the nomination of this lexico-thematic group and defines the floronomen forms as a separate thematic group of vocabulary, rich in connotations. The level of representation and the nomenclature variability of the designations are diverse. Floronomen, found in the works by Volodymyr Lys, can be clasified into several lexico-semantic subgroups: trees and shrubs, water, medicines, wild herbs and ornamental plants.